Social network analysis in a software crowdsourcing perspective - S. Machado, Leticia; M. Melo, Ricardo Rodrigo; R. B. de Souza, Cleidson (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2019: Anais do XV Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2019.7802, 2019)
Social network analysis (SNA) has been an important research tool in the Software Engineering community in the last years. The goal of this work is to bring together researcher and practitioners who have studied SNA from software crowdsourcing (SW CS) perspective, and to refine our ways of thinking about issues on communication and collaboration in SW CS projects.